Exploring the role of social work in perinatal mental health: a case study of postpartum depression intervention in Belize - Enriquez, Rowan; Oladeji, Olusola; Flowers, Angela (International Journal Of Community Medicine And Public Health, 2026)
Social workers play a vital role in addressing the mental health and social needs of perinatal women, often as key members of multidisciplinary teams. Postpartum depression (PPD) affects 10–20% of new mothers globally, posing risks to maternal well-being and infant development. Despite their importance, limited literature reviews the specific interventions social workers provide in PPD care. This study assesses the effectiveness of social work interventions for a first-time mother in Belize. This single-case intervention study employed a mixed-methods approach. MG, a 31-year-old first-time mother diagnosed with PPD, received eight biweekly online psychoeducational sessions (2–3 hours each) delivered by a licensed social worker between February and June 2025. Quantitative data were collected using the Edinburgh Postnatal Depression Scale (EPDS) and the Multidimensional Scale of Perceived Social Support (MSPSS) at baseline and post-intervention. Qualitative data were gathered through journaling and semi-structured interviews. Informed consent and confidentiality were maintained. MG’s EPDS score dropped from 15 to 2 post-intervention, an 87% reduction, moving from clinically significant to subclinical symptoms. MSPSS scores for family and significant others remained high (6), reflecting stable informal support. Qualitative findings showed improved emotional regulation, coping, and maternal confidence. Symptom reduction appears primarily linked to formal support via social work intervention. This study highlights the pivotal role of social workers in supporting women with PPD. Findings suggest that brief, low-cost, remotely delivered psychoeducational interventions can significantly improve maternal emotional health. Future research should explore scalability and integration into routine perinatal care in resource-limited settings.